Value-based Reimbursement as a Mechanism to Achieve Social and Financial Impact in the Healthcare System - Ana Paula Beck de Silva Etges; Harry H. Liu; Porter Jones; Carisi A. Polanczyk (Journal of Health Economics and Outcomes Research)
**Background:** Value-based reimbursement strategies have been considered in the continuous search for establishing a sustainable healthcare system. For models that have been already implemented, success is demonstrated according to specific details of the patients' consumption profile based on their clinical condition and the risk balance among all the stakeholders. From fee-for-service to value-based bundled payment strategies, the manner in which accurate patient-level cost and outcome information are used varies, resulting in different risk agreements between stakeholders. A thorough understanding of value-based reimbursement agreements that views such agreements as a mechanism for risk management is critical to the task of ensuring that the healthcare system generates social impacts while ensuring financial sustainability. This perspective article focuses on a critical analysis of the impact of value-based reimbursement strategies on the healthcare system from a social and financial perspective.